Effect of surface roughness on the mechanical properties in gradient structured pure copper - Cong Li; Huma Tabasum; Lele Sun; Xingfu Li; Zhilin Wu; Yulan Gong; Hongjiang Pan; Xinkun Zhu (Journal of Materials Research and Technology)
Gradient structured (GS) materials have been widely studied due to their excellent balance between strength and ductility. Surface mechanical attrition treatment (SMAT) can achieve grain refinement on the surface of materials, thereby obtaining gradient layers significantly impact the mechanical properties of materials. However, this processing method inevitably introduces high roughness on the surface. It cannot be ignored for the smoothness of the sample surface in a tensile test. In the present study, GS pure copper was prepared by SMAT. After fully annealing this gradient material in a vacuum environment and allowing the grains to grow completely (retaining the roughness caused by SMAT processing), it was found that its tensile mechanical properties were similar to those of fully annealed coarse-grained copper before SMAT processing. This indicates that the surface roughness of the sample is not an important factor affecting the tensile mechanical properties of pure GS copper. This work provides a meaningful insight into understanding the tensile mechanical behavior of gradient materials with high surface roughness.